Advances in Social and Occupational Ergonomics : Proceedings of the AHFE 2018 International Conference on Social and Occupational Ergonomics, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA /: Proceedings of the AHFE 2018 International Conference on Social and Occupational Ergonomics, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA. ([2019]) - Unknown
No abstract available